La posición de Levinas en el giro hermenéutico: el lenguaje como ética - Palacio, Marta (2013)
“Levinas’ standpoint in the hermeneutic turn: language as ethics”. This paper develops Emmanuel Levinas’ conceptions about language and its placein the linguistic-hermeneutic turn of contemporary philosophy. It examines the relations with the authors associated to this turn (Heidegger, Gadamer, Ricoeurand Derrida) due to the importance given to language and, at the same time, it sets him apart from them for his original ethical transmutation of language. This paper also considers the main philosophical notions by which Levinas treats the topic of language: desire, diachrony, the said and the saying, trace, absence, no-indifference, otherness.